1982
DOI: 10.1017/s0022112082003401
|View full text |Cite
|
Sign up to set email alerts
|

A simple model of mixing and chemical reaction in a turbulent shear layer

Abstract: Arguments are presented to show that the concept of gradient diffusion is inapplicable to mixing in turbulent shear layers. A new model is proposed for treating molecular mixing and chemical reaction in such flows a t high Reynolds number. It is based upon the experimental observations that revealed the presence of coherent structures and that showed that fluid elements from the two streams are distributed unmixed throughout the layer by large-scale inviscid motions. The model incorporates features of the stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
116
0
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(121 citation statements)
references
References 17 publications
4
116
0
1
Order By: Relevance
“…In the context of LES, a subgrid model for filamentation has been developed by Grabowski (2007) and Jarecka et al (2009) drawing on developments in combustion modelling. Grabowski (2007) proposed an advection-diffusion equation for the length scale, λ, of a filament based on the similarity arguments of Broadwell and Breidenthal (1982), who suggested that filaments of a conserved scalar field should obey…”
Section: Mechanisms For Entrainment In Cloudsmentioning
confidence: 99%
“…In the context of LES, a subgrid model for filamentation has been developed by Grabowski (2007) and Jarecka et al (2009) drawing on developments in combustion modelling. Grabowski (2007) proposed an advection-diffusion equation for the length scale, λ, of a filament based on the similarity arguments of Broadwell and Breidenthal (1982), who suggested that filaments of a conserved scalar field should obey…”
Section: Mechanisms For Entrainment In Cloudsmentioning
confidence: 99%
“…This section contains a brief description of the recent Broadwell-Breidenthal ( 1982) model for mixing and chemical reaction in a turbulent shear layer. It is discussed at this point since some of the results to be presented are interpreted in terms of the model.…”
Section: Broadwell-breidenthal Modelmentioning
confidence: 99%
“…The scaling arguments of Ref. [3] give the time for the interfacial area increase as comparable to the integral scale time τ I ∼ L=U. But in the time τ I diffusion produces a layer width…”
mentioning
confidence: 93%
“…The turbulent shear layer of neutral fluids provides a simplified paradigm for how the mix models of high density fusion are supposed to work. A model [3] for these shear layers computes the growth in time of the interfacial area, using scaling and similarity arguments that extend the homogeneous turbulence picture of Kolmogorov. The model [3] predicts that the interfacial area grows by a factor comparable to the ratio of the integral scale to the dissipation scale, or L=λ K ∼ R 3=4 e .…”
mentioning
confidence: 99%
See 1 more Smart Citation